To pollute or not to pollute? Decreasing the ecological footprint of pediatrics in the COVID-19 era - Yakup Gozderesi; Christos Tsagkaris; Anna Eleftheriades; Panagiota Pervanidou (Elsevier, 2022)
The climate crisis impacts child health, increasing the burden of pediatric healthcare. During the COVID-19 pandemic, the ecological footprint of pediatric healthcare has significantly increased due to the use of personal protective equipment and the provision of large-scale testing and vaccination against COVID-19. The situation calls for coordinated action to make pediatric healthcare more resource-efficient. To achieve this goal, pediatricians should work together with children and parents in order to appropriately minimize the use of electricity, water, paper and plastic and promote environmental sustainability in healthcare and beyond. The present article discusses the main sources of environmental pollution in pediatric healthcare and proposes evidence-based solutions.